PERANCANGAN SISTEM INVENTORY SPARE PARTS MOBIL PADA CV. AUTO PARTS TOYOTA BERBASIS APLIKASI JAVA - Yuhendra, MT , Dr.Eng; Rendi Poerwanta (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2013)
An Inventory System is a process to manage and find the items that function to obtain information about the existing stock of goods. In this this research focus in design inventory system automobile spare parts in CV Auto parts Toyota. The application was developed byt using Java and MySQL. With this system it will get easiness to obtain information about the existing inventory at the company.The use of the Inventory System has many shortcomings such as the duplication of data, due to the slow pace of factors both during the process of data entry, data retrieval and reporting processes. Overcome existing problems, then made an inventory system that can provide a solution in the management of spare part using Java applications so users work in the management of the inventory to be efficient and effective. In this design system and application, we get information stocks held in the storage of goods will become more efficient in terms of time and information obtained due to unnecessary check directly to the storage area.